Safety profile of gutless adenovirus vectors delivered into the normal brain parenchyma: Implications for a glioma phase 1 clinical trial - Ghulam Muhammad, A.K.M. (2012)
Adenoviral vectors (Ads) have been evaluated in clinical trials for glioma. However, systemic immunity against the vectors can hamper therapeutic efficacy. We demonstrated that combined immunostimulation and cytotoxic gene therapy provides long-term survival in preclinical glioma models. Because helper-dependent high-capacity Ads (HC-Ads) elicit sustained transgene expression, in the presence of antiadenoviral immunity, we engineered HC-Ads encoding conditional cytotoxic herpes simplex type 1 thymidine kinase and immunostimulatory cytokine Fms-like tyrosine kinase ligand-3 under the control of the TetOn system. Escalating doses of combined HC-Ads (1×10 8, 1×109, and 1×1010 viral particles [VP]) were delivered into the rat brain. We assessed neuropathology, biodistribution, transgene expression, systemic toxicity, and behavioral impact at acute and chronic time points after vector delivery. Histopathological analysis did not reveal any evidence of toxicity or long-term inflammation at the lower doses tested. Vector genomes were restricted to the injection site. Serum chemistry did not uncover adverse systemic side effects at any of the doses tested. Taken together, our data indicate that doses of up to 1×109 VP of each HC-Ad can be safely administered into the normal brain. This comprehensive toxicity and biodistribution study will lay the foundations for implementation of a phase 1 clinical trial for GBM using HC-Ads.